2006
DOI: 10.1590/s1020-49892006001000002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against measles, mumps, and rubella before and after vaccination of school-age children with three different triple combined viral vaccines, Rio Grande do Sul, Brazil, 1996

Abstract: About one-fifth (20.8%) of the schoolchildren who could have been vaccinated against measles at age 9 months had levels of antibodies insufficient for protection. In the sample of schoolchildren without previous vaccination against mumps and rubella, high proportions of susceptible levels were found. All vaccines were immunogenic, but vaccine A yielded a seroconversion rate of 99.5% for the mumps component, which was significantly higher than the other two vaccines (P<0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…In comparison to a previous study in South Africa which reported 9% of children with meningitis to have mumps virus, the reported seropositivity in this current study is indeed high [20]. When compared to previous studies in other countries outside Africa; the reported seropositivity in the current study is low compared to 80.2%, 71.9%, 89.1, 71.1 and 69.4% reported in Iran, Yemen, Ankara Turkey, Eastern Turkey and Brazil, respectively [1,18,24,29,30]. The possible explanation for these variations could be due to differences in seasonality, study populations, geographical and climatic conditions.…”
Section: Discussionsupporting
confidence: 45%
“…In comparison to a previous study in South Africa which reported 9% of children with meningitis to have mumps virus, the reported seropositivity in this current study is indeed high [20]. When compared to previous studies in other countries outside Africa; the reported seropositivity in the current study is low compared to 80.2%, 71.9%, 89.1, 71.1 and 69.4% reported in Iran, Yemen, Ankara Turkey, Eastern Turkey and Brazil, respectively [1,18,24,29,30]. The possible explanation for these variations could be due to differences in seasonality, study populations, geographical and climatic conditions.…”
Section: Discussionsupporting
confidence: 45%
“…These studies were conducted in Brazil (1), Mexico (3), Sweden (1), the U.S., and U.S./Europe (1). [14][15][16][17][18][19][20] The mean age of participants ranged from 7 to 26 years (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%